POWDER SOLUTION TECHNOLOGY REVIEW - SHARMA, SHAVETA; ARORA, VIMAL (International Journal of Current Pharmaceutical Research, 2021)
Bioavailability and Solubility are the challenges for the formulation of highly lipophilic drugs. Oral routes of administration is one of the acceptable route due to improved patient compliance and convenience. Regularly newly advanced drug candidates are lipophilic, BCS Class II and IV drugs. Among various methods to improve the solubility of these drugs, liquid-solid technology or Powdered solution technology change the liquid drug into non-sticky, dry free-flowing, rapid release powder. This technique involves mixing of insoluble drug with nonvolatile solvent, admixing of drug-loaded excipients change into loose powder. This technique enhances major challenges like bioavailability with low production cost and a simple manufacturing process.